2020
DOI: 10.1519/jsc.0000000000003201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Personal Protective Equipment on the Performance of Federal Highway Policemen in Physical Fitness Tests

Abstract: Marins, EF, Cabistany, L, Bartel, C, Dawes, J, and Del Vecchio, FB. Effects of personal protective equipment on the performance of Federal Highway Policemen in physical fitness tests. J Strength Cond Res 34(1): 11–19, 2020—Personal protective equipment (PPE), worn by police officers, provides protection and can modify physiological and performance responses during physical efforts. Physiological, perceptual, and physical responses were compared with PPE (WPPE) and without PPE (NPPE) among the Brazilian Federal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…These results are in line with the findings of this study, where the mean V Ȯ2 max value measured indirectly from a 2.4-km run is 45 mlO 2 •kg 21 •min 21 and the result from 2.4-km run is 793 seconds. The accumulating evidence has shown that most studies estimate aerobic capacity from indirect measures, i.e., the Cooper test, 2.4-km run, 1.6-km run, and the 20-m multiple shuttle-run test (14). Findings for both 2.4-km run and indirect V Ȯ2 max measures in "very poor" (,20th percentile) and "poor" (20th-40th percentile) vs. "high" (60th-80th percentile) and "very high" (.80th percentile) aerobic capacity level may add a significant guideline in detecting those applicants with lower cardiorespiratory fitness level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are in line with the findings of this study, where the mean V Ȯ2 max value measured indirectly from a 2.4-km run is 45 mlO 2 •kg 21 •min 21 and the result from 2.4-km run is 793 seconds. The accumulating evidence has shown that most studies estimate aerobic capacity from indirect measures, i.e., the Cooper test, 2.4-km run, 1.6-km run, and the 20-m multiple shuttle-run test (14). Findings for both 2.4-km run and indirect V Ȯ2 max measures in "very poor" (,20th percentile) and "poor" (20th-40th percentile) vs. "high" (60th-80th percentile) and "very high" (.80th percentile) aerobic capacity level may add a significant guideline in detecting those applicants with lower cardiorespiratory fitness level.…”
Section: Discussionmentioning
confidence: 99%
“…Police officers often require having physical fitness at higher level, because of specific tasks and demands of running, jumping, carrying heavy objects, and being concentrated (8,13). Numerous studies have been conducted regarding the level of physical fitness in police officers (1,6,8,9,(12)(13)(14)16,17). In general, the most recent systematic review has shown that police officers have "good" aerobic capacity, "better" musculoskeletal power, and "regular" (for men) and "good" (for women) flexibility, when comparing with general population (14).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carrying excessive load represents a main physical activity for duty officers, especially police [ 1 ]. Police officers are considered as performing at the maximal level, executing highly demanding everyday activities, including running, jumping and carrying heavy objects [ 2 , 3 ]. Such extreme loading conditions may lead to a deviated foot function and structure [ 4 ].…”
Section: Introductionmentioning
confidence: 99%